Lessons learned from the 1‐hour post‐load glucose level during OGTT: Current screening recommendations for dysglycaemia should be revised. Issue 5 (24th March 2018) - Bergman, Michael; Jagannathan, Ram; Buysschaert, Martin; Pareek, Manan; Olsen, Michael H.; Nilsson, Peter M.; Medina, José Luis; Roth, Jesse; Chetrit, Angela; Groop, Leif; Dankner, Rachel
Abstract: This perspective covers a novel area of research describing the inadequacies of current approaches for diagnosing dysglycaemia and proposes that the 1‐hour post‐load glucose level during the 75‐g oral glucose tolerance test may serve as a novel biomarker to detect dysglycaemia earlier than currently recommended screening criteria for glucose disorders. Considerable evidence suggests that a 1‐hour post‐load plasma glucose value ≥155 mg/dl (8.6 mmol/L) may identify individuals with reduced β‐cell function prior to progressing to prediabetes and diabetes and is highly predictive of those likely to progress to diabetes more than the HbA1c or 2‐hour post‐load glucose values. An elevated 1‐hour post‐load glucose level was a better predictor of type 2 diabetes than isolated 2‐hour post‐load levels in Indian, Japanese, and Israeli and Nordic populations. Furthermore, epidemiological studies have shown that a 1‐hour PG ≥155 mg/dl (8.6 mmol/L) predicted progression to diabetes as well as increased risk for microvascular disease and mortality when the 2‐hour level was <140 mg/dl (7.8 mmol/L). The risk of myocardial infarction or fatal ischemic heart disease was also greater among subjects with elevated 1‐hour glucose levels as were risks of retinopathy and peripheral vascular complications in a Swedish cohort. The authors believe that the considerable evidence base supports redefining current screening and diagnostic recommendations with the 1‐hour post‐load level. Measurement of the 1‐hour PG level would increase the likelihood of identifying a larger, high‐risk group with the additional practical advantage of potentially replacing the conventional 2‐hour oral glucose tolerance test making it more acceptable in a clinical setting.